ANALISIS KETERAMPILAN BERBICARA BAHASA JERMAN MAHASISWA STAMBUK 2023 UNIVERSITAS NEGERI MEDAN - Ghina Hilwani Salsabila; Mawarni Br Sitanggang; Erika Sahruni; Dwi Nabilla Putri; Rina Evianty (Berugak Baca, 2025)
This article aims to determine the level of German speaking ability A1 in Stambuk 2023 students at Medan State University. This research use desciptive qualitative approach. The sample in this study were all students of class A standard 2023 at Medan State University. The sampling technique uses the Simple Random Sampling technique. The data collection technique uses a questionnaire.The results of this research show the level of German language skills possessed by students of the 1st semester German language study program who are in class A. Respondents consisting of 10 students admitted that it was easy to learn German on the Sich Vorstellen theme and they said they were able to introduce themselves in German.